Concentration, Price, and Critical Concentration Ratios - Geithman, Frederick E.; Marvel, Howard P.; Weiss, Leonard W. (The Review of Economics and Statistics, 1981)
A potentially important parameter that has not yet been convincingly estimated is the critical concentration ratio. This paper attempts to estimate it in three types of market. The estimation of a critical concentration ratio, if one exists, seems of potentially great importance because of its implication for antitrust policy. If a critical concentration ratio were found and if concentration had no effect below that level, it would seem to follow that a horizontal merger in a market where concentration was below the critical level and where the merger could not increase concentration to the critical level could not substantially lessen competition or tend to create monopoly.